A novel criterion to identify coatings' adhesion. (3rd April 2022) - Xu, Shuai; Li, Jinlong; Zhou, Yanwen; Zhang, Kaice
ABSTRACT: A novel criterion, plastic/elastic deformation work (Wp /We ), was introduced to identify the co-deformation capacity of chromium–nitrogen (Cr–N) coating and titanium alloy system, which can be related to the coating/substrate adhesion. By changing the N2 flow ( f N2 ), the Cr–N coatings were deposited on Ti6Al4V (TC4) alloy substrate to obtain Cr(N), Cr2 N and/or CrN coatings, which could be related to the various deformation capacities. It indicated that the high Wp /We ratios of the metallic Cr(N)/TC4 systems deformed coordinately and attached well. Among the ceramic CrNx /TC4 systems, the single-phase CrN/TC4 exhibited higher Wp /We ratio of 1.71 than 1.52 and 1.61 of the Cr2 N or Cr2 N@CrN/TC4 and better adhesion. As a novel criterion, Wp /We ratio indicates the co-deformation capacity of a coating/alloy system, related to the failure mechanism and the adhesion of a coating to the substrate.